Absence of Desmin Results in Impaired Adaptive Response to Mechanical Overloading of Skeletal Muscle - Joanne, Pierre; Hovhannisyan, Yeranuhi; Bencze, Maximilien; Daher, Marie-Thérèse; Parlakian, Ara; Toutirais, Geraldine; Gao-Li, Jacqueline; Lilienbaum, Alain; Li, Zhenlin; Kordeli, Ekaterini; Ferry, Arnaud; Agbulut, Onnik (Frontiers in Cell and Developmental Biology, 2021)
Background. Desmin is a muscle-specific protein belonging to the intermediate filament family. Desmin mutations are linked to skeletal muscle defects, including inherited myopathies with severe clinical manifestations. The aim of this study was to examine the role of desmin in skeletal muscle remodeling and performance gain induced by muscle mechanical overloading which mimics resistance training. Methods. Plantaris muscles were overloaded by surgical ablation of gastrocnemius and soleus muscles. The functional response of plantaris muscle to mechanical overloading in desmin-deficient mice (DesKO, n=32) was compared to that of control mice (n=36) after 1-month overloading. To elucidate the molecular mechanisms implicated in the partial adaptive response of DesKO muscle, we examined the expression levels of genes involved in muscle growth, myogenesis, inflammation and oxidative energetic metabolism. Moreover, ultrastructure and the proteolysis pathway were explored. Results. Contrary to control, absolute maximal force did not increase in DesKO muscle following mechanical overloading. Fatigue resistance was also less increased in DesKO as compared to control muscle. Despite impaired functional adaptive response of DesKO mice to mechanical overloading, muscle weight and the number of oxidative MHC2a-positive fibers per cross-section similarly increased in both genotypes. However, OVL-elicited remodeling failed to activate normal myogenic program, resulting in proportionally reduced activation and differentiation of muscle stem cells. Ultrastructural analysis of the plantaris muscle after 1-month overloading revealed muscle fiber damage in DesKO, as indicated by the loss of sarcomere integrity and mitochondrial abnormalities. Moreover, the observed accumulation of autophagosomes and lysosomes in DesKO muscle fibers could indicate a blockage of autophagy. To address this issue, two main proteolysis pathways, the ubiquitin-proteasome system and autophagy, were explored in DesKO and control muscle. Our results suggested an alteration of proteolysis pathways in DesKO muscle in response to mechanical overloading. Conclusion. Taken together, our results show that mechanical overloading increases the negative impact of the lack of desmin on myofibril organization and mitochondria. Furthermore, our results suggest that under these conditions, the repairing activity of autophagy is impaired. Consequently, force generation is not improved despite muscle growth, suggesting that desmin is required for a complete response to resistance training in skeletal muscle.